2020
DOI: 10.3390/brainsci10070430
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Randomized Trial for an Intensive Memory-Focused Training Program for School-Aged Children with Acquired Brain Injury

Abstract: (1) Background: Memory deficits are common sequelae of pediatric Acquired Brain Injury (ABI). Only methods for non-focused cognitive remediation are available to the pediatric field. The aims of this feasibility trial are the description, implementation, and test of an intensive program specific to the training and re-adaptation of memory function in children, called Intensive Memory-Focused Training Program (IM-FTP); (2) Methods: Eleven children and adolescents with ABI (mean age at injury = 12.2 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A randomized controlled study of children with central nervous system injuries found that a cognitive remediation program (CRP) improved both attention and academic performance ( 64 ). Recla et al showed that a 1-month intensive memory-focused training program (IM-FTP) improved children's ability to learn semantically related and irrelevant words, while also improving their immediate prose memory ( 65 ). Functional magnetic resonance imaging (fMRI) analyses of these children revealed that the IM-FTP treatment was associated with functional changes in the left lower frontal cortex.…”
Section: Treatment Of Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized controlled study of children with central nervous system injuries found that a cognitive remediation program (CRP) improved both attention and academic performance ( 64 ). Recla et al showed that a 1-month intensive memory-focused training program (IM-FTP) improved children's ability to learn semantically related and irrelevant words, while also improving their immediate prose memory ( 65 ). Functional magnetic resonance imaging (fMRI) analyses of these children revealed that the IM-FTP treatment was associated with functional changes in the left lower frontal cortex.…”
Section: Treatment Of Cognitive Impairmentmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) analyses of these children revealed that the IM-FTP treatment was associated with functional changes in the left lower frontal cortex. The left lower frontal gyrus is closely associated with the left posterior middle temporal gyrus, which plays a vital role in syntactic analysis ( 66 ) and vocabulary selection ( 67 ), which is why this is an area that is stimulated during intensive memory training ( 65 ).…”
Section: Treatment Of Cognitive Impairmentmentioning
confidence: 99%